Measurement of expansion factor and distortion for expansion microscopy using isolated renal glomeruli as landmarks. Issue 7 (27th April 2021) - Zhu, Chen; Wang, Aidong; Chen, Lili; Guo, Liangsheng; Ye, Jiajia; Chen, Qilin; Wang, Qi; Yao, Guojia; Xia, Qin; Cai, Tianyu; Guo, Jiayun; Yang, Zhenyu; et al.
Abstract: Expansion microscopy has enabled super resolution imaging of biological samples. The accurate measurement of expansion factor and distortion typically requires locating and imaging the same region of interest in the sample before and after expansion, which is often time‐consuming to achieve. Here we introduce a convenient method for relocation by utilizing isolated porcine glomeruli as landmarks during expansion. Following heat denaturation and proteinase K digestion protocols, the glomeruli exhibit expansion factor of 3.5 to 4 (only 7%‐16% less expanded than the hydrogel), and 1% to 2% of relative distortion. Due to its appropriate size of 100 to 300 μm, the location of the glomerulus in the sample are visible to eyes, while its detailed shape only requires bright field microscopy. For expansion factors ranging from 3 to 10, the region in the vicinity of the glomerulus can be easily re‐identified, and sometimes allows quantification of expansion factor and distortion under bright field without fluorescent labels. Abstract : The porcine glomeruli, due to their appropriate size, structure and rigidity, have now been seriously utilized as the landmarks for keeping track of regions of interest and quantifying sample expansion at microscopic scales for expansion microscopy.